استلحاق ولد الزنا في الفقه الإسلامي وقانون الأحوال الشخصية الأردني - أبو ليل، محمد محمود أحمد (جامعة آل البيت, 2019)
جاءت هذه الدراسة؛ لتعالج مشكلة الأولاد الناتجين عن الزنا، وبيان كيفية المحافظة على حقوقهم الشرعية، وتبرز أهمية هذا الموضوع من خلال بحثه في الإجراءات العلاجية لأهم آثار جريمة الزنا، التي حذرت منها نصوص الشريعة، وعدتها من الكبائر والجرائم التي تهدد بنيان المجتمع وسلامته. كما بينت الدراسة اهتمام الشريعة الإسلامية بالنسب بوصفه من الضروريات الخمس التي قامت أحكامها على رعايتها وحفظها. كما بينت الدراسة أن العلماء قد اتفقوا على نسبة ولد الزنا لأمه بمجرد الولادة، أما إذا حملت المرأة من زنا، وكانت خلية، وأراد الزاني أن يستلحقه، فللعلماء فيه ثلاثة أقوال، وقد رجحت هذه الدراسة رأي الجمهور وهو أنه لا يثبت ولد الزنا إلى الزاني ولو استلحقه.
This study aims to address the issue of children who came from adultery, and shows how to preserve their legitimate rights. The importance of this issue is reflected by discussing the remedial measures of the most important consequences of the crime of adultery, which was warned by Sharia, and considered as a major sin and a crime that threaten the society and its safety. The study also showed the interest of Islamic Sharia in lineage as one of the five essentials which was protected and maintained by Sharia’s provisions. The study also showed that the scholars agreed to the annexation of the son of adultery to his mother once delivered. In case the unmarried woman got pregnant after committing adultery and the adulterer wants to have the son’s annexation to his side, the scholars provided three opinions. This study adopts the view of the majority of scholars which says that the son of adultery does not annex to the adulterer, even if he annexed him.
Keywords: الفقه الإسلامي -- القوانين والتشريعات -- قانون الأحوال الشخصية -- الأردن